Aerobic and anaerobic endurance of disabled swimmers in special preparation sub-period - Szafraniec, R.; Seidel, W.; Kruszyna, D.; Zurowska, A. (Baltic Journal of Health and Physical Activity, 2012)
Background: The purpose of the study was to investigate whether, in addition to an expected increase in anaerobic endurance, aerobic endurance of disabled swimmers would also improve in a special preparation sub-period. Furthermore, decision was made to examine whether the applied tests prove sufficiently sensitive for swimmers with disabilities as well.